Biodiversity maintains soil multifunctionality and soil organic carbon in novel urban ecosystems. (20th March 2022) - Schittko, Conrad; Onandia, Gabriela; Bernard‐Verdier, Maud; Heger, Tina; Jeschke, Jonathan M.; Kowarik, Ingo; Maaß, Stefanie; Joshi, Jasmin
Abstract: Biodiversity in urban ecosystems has the potential to increase ecosystem functions and support a suite of services valued by society, including services provided by soils. Specifically, the sequestration of carbon in soils has often been advocated as a solution to mitigate the steady increase in CO2 concentration in the atmosphere as a key driver of climate change. However, urban ecosystems are also characterized by an often high level of ecological novelty due to profound human‐mediated changes, such as the presence of high numbers of non‐native species, impervious surfaces or other disturbances. Yet it is poorly understood whether and how biodiversity affects ecosystem functioning and services of urban soils under these novel conditions. In this study, we assessed the influence of above‐ and below‐ground diversity, as well as urbanization and plant invasions, on multifunctionality and organic carbon stocks of soils in non‐manipulated grasslands along an urbanization gradient in Berlin, Germany. We focused on plant diversity (measured as species richness and functional trait diversity) and, in addition, on soil organism diversity as a potential mediator for the relationship of plant species diversity and ecosystem functioning. Our results showed positive effects of plant diversity on soil multifunctionality and soil organic carbon stocks along the entire gradient. Structural equation models revealed that plant diversity enhanced soil multifunctionality and soil organic carbon by increasing the diversity of below‐ground organisms. These positive effects of plant diversity on soil multifunctionality and soil fauna were not restricted to native plant species only, but were also exerted by non‐native species, although to a lesser degree. Synthesis . We conclude that enhancing diversity in plants and soil fauna of urban grasslands can increase the multifunctionality of urban soils and also add to their often underestimated but very valuable role in mitigating effects of climate change. Abstract : Our study highlights the positive effects of plant diversity on soil functioning in urban areas. By investigating dry grassland soils in Berlin, Germany, we show that plant diversity enhanced soil multifunctionality and soil organic carbon by increasing the diversity of below‐ground organisms. These positive effects of plant diversity were not restricted to native plant species only, but were also exerted by non‐native species, although to a lesser degree.